2003
DOI: 10.1002/chem.200204674
|View full text |Cite
|
Sign up to set email alerts
|

Highly Diastereoselective [3+2] Cycloadditions between Nonracemic p‐Tolylsulfinimines and Iminoesters: An Efficient Entry to Enantiopure Imidazolidines and Vicinal Diaminoalcohols

Abstract: A new procedure for the asymmetric synthesis of imidazolidines and vicinal diamines is reported. The 1,3-dipolar cycloaddition between nonracemic p-tolylsulfinimines and azomethine ylides generated in situ from alpha-iminoesters and LDA produces N-sulfinylimidazolidines with a high degree of stereocontrol. In contrast, the presence of Lewis acids promotes formation of the cycloadducts through a highly diastereoselective process with opposite stereochemistry. Subsequent transformations of the imidazolidines inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 92 publications
1
22
0
Order By: Relevance
“…The resulting β-amino deprotected syn -γ-chloro-α,β-diaminocarboxylamide could subsequently ring close further to trans -imidazolidine 12b , which will be less sterically congested than an analogous cis -imidazolidine. In the literature, comparable non-halogenated trans -imidazolidines were already synthesized by 1,3-dipolar cycloaddition of N -benzylidene glycine ester enolates across N -sulfinylaldimines in the presence of a Lewis acid [43]. The trans -stereochemistry of imidazolidine 12b was ensured by the vicinal coupling constant 3 J H4-H5 = 7.43 Hz and the 1 H NMR chemical shift of H4 (3.85 ppm), which were in the same range as for closely related trans -imidazolidines and trans -oxazolidines [4345].…”
Section: Resultsmentioning
confidence: 99%
“…The resulting β-amino deprotected syn -γ-chloro-α,β-diaminocarboxylamide could subsequently ring close further to trans -imidazolidine 12b , which will be less sterically congested than an analogous cis -imidazolidine. In the literature, comparable non-halogenated trans -imidazolidines were already synthesized by 1,3-dipolar cycloaddition of N -benzylidene glycine ester enolates across N -sulfinylaldimines in the presence of a Lewis acid [43]. The trans -stereochemistry of imidazolidine 12b was ensured by the vicinal coupling constant 3 J H4-H5 = 7.43 Hz and the 1 H NMR chemical shift of H4 (3.85 ppm), which were in the same range as for closely related trans -imidazolidines and trans -oxazolidines [4345].…”
Section: Resultsmentioning
confidence: 99%
“…Chiral sulfinimines, readily available in both enantiomeric forms, have proven to be valuable intermediates for the synthesis of different nitrogen-containing targets. 77 Viso et al [78][79][80] reported the asymmetric synthesis of enantiopure N-sulfinyl imidazolidines 176 via a diastereoselective 1,3-dipolar cycloaddition between readily available p-toluenesulfinimines 174 and glycine iminoester enolates 175 (Scheme 33).…”
Section: Cyclization At C 3 -Nmentioning
confidence: 98%
“…Reductive [78][79][80] or hydrolytic cleavage 81 of the aminal moiety transformed N-sulfinyl imidazolidines 176 into differently protected vicinal diamino alcohols 177 and N-sulfinyl diamino esters 179, respectively. These classes of compounds are potential substrates for the synthesis of enantiopure N-sulfinyl piperazinones 178 and 180, respectively, bearing suitable arms for further functionalizations.…”
Section: Cyclization At C 3 -Nmentioning
confidence: 99%
See 1 more Smart Citation
“…p-Toluenesulfinimines 11 can participate as chiral inductors in the BF 3 ÁEt 2 O-mediated addition of lithiated a-imino glycinates to afford enantiopure 4,5-trans 4-carbomethoxy N-sulfinylimidazolidines 12 (Scheme 9.2). Interestingly in the absence of BF 3 ÁEt 2 O, enolates derived from phenylalanine, alanine, and leucine treated with lithium diisopropylamide (LDA) provide imidazolidines 12a containing quaternary centers with endo stereocontrol and excellent diastereofacial discrimination of the chiral sulfiminine [10]. Subsequently, enantiopure syn N-sulfinyl-a,b-diamino esters 13 can be selectively produced under acidic conditions modulated by choosing a non-nucleophilic solvent [tetrahydrofuran (THF) : H 2 O versus MeOH] to preserve the sulfinamide moiety and thus achieve different degrees of functionalization at the amino groups [11].…”
Section: Reaction Of Glycinates and Related Nucleophiles With Electromentioning
confidence: 99%